An improved synthesis of vinyl- and β-iodovinyl sulfones by a molecular iodine-mediated one-pot iodosulfonationdehydroiodination reaction - Tassaporn Sawangphon (2018)
An improved one-pot method to synthesize vinyl sulfones from unsaturated systems by using molecular iodine/sodium arenesulfinate/sodium acetate as reagents was described. Vinyl sulfones derived from styrene derivatives were generally obtained in good to excellent yields except for those bearing strong electron releasing substituent. Aliphatic alkenes and activated alkenes gave the corresponding vinyl sulfone products in moderate to good yields. Arylacetylenes yielded the respective β-iodovinyl sulfones in good yields while low yield was observed with aliphatic terminal alkyne. The potentials of the method entail simplicity, short reaction time, non-anhydrous reaction conditions, employing inexpensive, non-metallic reagent and integrating two reactions that are commonly accomplished separately into a single operation. Supplemental materials are available for this article. Go to the publisher's online edition of Synthetic Communications® to view the free supplemental file. Copyright © Taylor & Francis Group, LLC.